A force‐based fiber beam‐column element to predict moment‐axial‐shear interaction of reinforced concrete frames. (11th June 2021) - Hippola, Sameera; Rajapakse, Chathura; Mihaylov, Boyan; Wijesundara, Kushan
Abstract: The nonlinear analysis of large complex reinforced concrete (RC) frame structures with shear‐critical members requires numerical approaches that combine high accuracy and computational efficiency. At the same time, existing modeling approaches either involve detailed and costly discretization of the deformations in the frame members (displacement‐based approaches), or compromise on accuracy by greatly simplifying (or even neglecting) shear effects. This paper presents a novel nonlinear force‐based fiber beam‐column element that addresses both these challenges. The element is capable of capturing the complex moment‐axial‐shear interaction response of planar RC frames and walls, while at the same time requiring minimum discretization. The proposed formulation consists of two nested iterative procedures at the structure and sectional levels. The introduction of the sectional level procedure explicitly satisfies sectional equilibrium, which is not achieved in either existing displacement or force‐based line element formulations. As a result, a stable convergence of all average strain, local crack strain, and slip strain components of the constitutive relationship is ensured. The efficiency and accuracy of the proposed element formulation is illustrated with the help of beam and frame tests from the literature.